The lifestyle of institutionalized hypertensive elderly – an analysis focusing on health education - Juliana Lima Fonteles; Zélia Maria de Sousa Araújo Santos; Marlucilena Pinheiro da Silva (Rev Rene)
Arterial hypertension is controlled with healthy life style. This qualitative descriptive study aimed at describing the perception of the 21 hypertensive elderly about lifestyle, for the control of hypertension, attending a daycare center called Lar da Melhor Idade, in Aquiraz-CE. The age of the elderly varied between 60 and 83 years. Six of them were man and fifteen were women. For those, the lifestyle consisted of a set of acts and attitudes concerning the daily reality of each one, regarding survival issues such as working, sleeping, resting, eating and economic situation. Eight elderly subjects associated healthy lifestyle to the consumption of healthy food, to health, to well being, to leisure, to regular practice of physical exercise and to alcohol and tobacco abstinence. Therefore, the healthy lifestyle in the conception of the subject exceeded the health matter and emerged from their beliefs, principles, and their socioeconomic conditions.